Debt and its velocity as determinants of real economic activity - Boháčik, Ján (2026)
The reality of the last decades shows us that debt has an important place in modern economies. This thesis focuses on debt in the form of bank loans extended to private economic agents – households and corporates. It explores the causal relationship between debt and real economic activity, expressed in terms of aggregate income, consumption, and corporate default rates. Debt is analyzed not only in absolute terms but also in relation to other factors – namely, its velocity is the object of interest. The income velocity of debt serves as a valuable tool for investigating the relationship between debt and aggregate income, as well as for interpreting how financial shocks transition into the real economy. The transmission of the changes in debt to real economic activity is inherently complex and the research gap especially lies in the absence of in-depth transmission of loan dynamics to certain aspects of the real economy (aggregate income, household consumption and corporate default rate). Therefore, the presented analysis accounts for various relevant variables, such as (but not limited to) distribution of income and wealth, distribution of marginal propensity to consume, financial and non-financial (housing) wealth, policy interest rates, and prudential policies. The first paper discusses the interaction of debt and economic performance and the models making provision for debt. The paper demonstrates how financial shocks affect the income velocity of money under different distributions of wealth/income and marginal propensity to consume across the population. For this purpose, an original agent-based simulation model with a limited loan supply was designed. Proposed model shocks are shocks to loan demand, loan supply, marginal propensity to consume, macro-prudential regulatory ratios, real estate capital gains, repayment ratios, shocks to the structure of loans provided and to the structure of real estate property transactions.